Metode dan Pendekatan Pendidikan Karakter Perspektif Pendidikan Islam - Muhyidin Muhyidin (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2022)
National character has a very strategic role in determining the progress and fall of a nation. So it is not a coincidence that the Prophet Muhammad. sent with the mission of perfecting morals or building human character. In the context of national education, character building programs have been proclaimed from one era of national leadership to another. In the reform era, an official character education program was launched in formal educational institutions in 2010, with the aim of improving the nation's morality which had experienced degradation. The implementation of the program is carried out by preparing a grand design and guidelines for implementing character education in schools. In order to enrich the discourse around the program, this article will discuss a formulation of character education in the perspective of Islamic education which includes three pillars, namely the foundations, methods and approaches to education which are conceptualized from the Al-Quran and Sunnah. This formulation is expected to be applied in Islamic educational institutions such as madrasas, even in non-formal educational institutions such as Islamic boarding schools and families